Implementación de un Sistema de Control Aplicado al Posicionamiento de un robot Stewart-Gough didáctico, para seguir el movimiento de un foco de luz. - Altamirano Changoluisa, Mayra Estefanía (2017)
This document presents the implementation of a control system applied to the positioning of a Stewart-Gough didactic robot, to follow the movement of a source of light. A closed loop control was used because it is necessary to know the value of the voltages in each of the sensors as well as the distances the linear actuators. For the mechanical implementation of the Stewart-Gough platform it was necessary to use accessories such as universal and rotary joints that allow the rotational and translational movements of the linear actuators with regard to the mobile platform and base it fixes. In the control of closed bow (Feedback) different tests of calibration were realized in the voltages got for the photovoltaic panels and actuators linear, across the analogical digital conversion (A/D) that provides the card Arduino Mega 2560 for his corresponding comparisons and conditions in the programming of the software Matlab, obtaining the movements different from the platform Stewart-Gough. There developed an interface human being - machine (HMI) with amicable characteristics for the user; same that consists of a manual and automatic control; that possesses 3 windows different from process in which the user will be able to handle in a didactic way the platform Stewart-Gough.